2013
DOI: 10.3109/00498254.2013.839847
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and mass balance of SGLT2 inhibitor tofogliflozin following oral administration to humans

Abstract: 1. Tofogliflozin is a novel and selective SGLT2 inhibitor increasing glucosuria by inhibition of glucose re-absorption in the kidney for the treatment of type 2 diabetes mellitus. 2. In this study, the metabolism and the mass balance of tofogliflozin was evaluated following administration of a single oral dose of 20 mg [(14)C]-tofogliflozin to six healthy subjects. 3. Tofogliflozin underwent mainly oxidative metabolism in the ethylphenyl moiety, but also minor glucuronide conjugates of metabolites and the pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 7 publications
5
27
0
Order By: Relevance
“…14 C]tofogliflozin to healthy subjects was 1814, 2215, 225, and 136 ng h/mL for tofogliflozin, M1, M2/ M3, and M5, respectively, and that M1 was found to be the major metabolite in urine and feces (Zell et al, 2013). These results suggested that the main metabolite of tofogliflozin was M1 in human.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…14 C]tofogliflozin to healthy subjects was 1814, 2215, 225, and 136 ng h/mL for tofogliflozin, M1, M2/ M3, and M5, respectively, and that M1 was found to be the major metabolite in urine and feces (Zell et al, 2013). These results suggested that the main metabolite of tofogliflozin was M1 in human.…”
Section: Discussionmentioning
confidence: 48%
“…M2/M3 and M5 are also considered not to affect the in vivo efficacy: the AUC 0-24h values of M2/M3 and M5 were 225 and 136 ng h/ mL, respectively (Zell et al, 2013), and in vivo potency of M2/M3 and M5 versus tofogliflozin was estimated to be 0.2 and 0.1, respectively, even when their f p was 1. Because the exposure of M4 was undetectable (Zell et al, 2013), it was considered that it would not influence in vivo efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The urinary excretion of tofogliflozin and empagliflozin in humans has been reported to be $20% of the dose (Macha et al, 2014;Zell et al, 2014). Because the urinary excretion is greater than the glomerular filtrated amount, estimated from the plasma unbound AUC of the drug, these drugs are thought to be secreted in the renal tubules.…”
Section: Discussionmentioning
confidence: 97%
“…An in vitro study has shown that tofogliflozin is metabolized by enzymes CYP2C18, 3A4/5, 4A11, and 4F3B [11]. Mass balance studies have shown that tofogliflozin in systemic circulation is eliminated mainly by metabolism, and a major part (75.5 % of the dose) of tofogliflozin and its metabolites is eliminated by urinary excretion [9,12].…”
Section: Introductionmentioning
confidence: 99%